2006
DOI: 10.1002/nme.1588
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkle/slack model and finite element dynamics of membrane

Abstract: SUMMARYThis paper reviews conventional wrinkle models for anisotropic membrane and shows the relation between the models. A new wrinkle model is proposed which assumes virtual shear as well as virtual elongation of the membrane to estimate the real strain in the wrinkled region. This model coincides with the other models if the virtual shear and elongation is determined so that the strain energy is minimized. Another wrinkle/slack model is proposed for the dynamic analysis of thin isotropic membrane undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Therefore, Miyazaki, et al proposed methods to represent the area and intensity of the wrinkles by giving some small compressive stiffness in the wrinkle direction. One of the methods is the stiffness reduction model (SRM), which is a model to give compressive stiffness as a ratio of the tensile stiffness (Miyazaki, 2006), and another is the maximum compressive stress model (MCSM), which does not permit the compressive stress to exceed a certain value (Miyazaki and Arita, 2008). However, the methods for determining the compressive stiffness are not established, and the distribution of principal stress in slack areas is not valid (Inoue, 2009).…”
Section: Previous Studymentioning
confidence: 99%
“…Therefore, Miyazaki, et al proposed methods to represent the area and intensity of the wrinkles by giving some small compressive stiffness in the wrinkle direction. One of the methods is the stiffness reduction model (SRM), which is a model to give compressive stiffness as a ratio of the tensile stiffness (Miyazaki, 2006), and another is the maximum compressive stress model (MCSM), which does not permit the compressive stress to exceed a certain value (Miyazaki and Arita, 2008). However, the methods for determining the compressive stiffness are not established, and the distribution of principal stress in slack areas is not valid (Inoue, 2009).…”
Section: Previous Studymentioning
confidence: 99%
“…18 confirm that the membrane is deployed smoothly by the deployment mechanism. The multi-particle model and the finite element method model 9) shown in Fig. 19 are used mainly to predict the deployment dynamics.…”
Section: Deployment Systemmentioning
confidence: 99%
“…First, we briefly describe the conventional wrinkling theory by Roddeman et al [20] and modifications by other researchers [7,8,14]. Then we combine this with the quadrilateral Cosserat point formulation.…”
Section: Analysis Of Wrinklesmentioning
confidence: 99%
“…Similar approaches have also been developed for anisotropic [2,10] and orthotropic [19,30] membranes. Miyazaki [14] has critically reviewed many of these approaches and concluded that all the approaches are essentially the same. The last author has also proposed a model based on virtual elongation and virtual shear of the membrane to estimate the real strain in the wrinkled region.…”
Section: Introductionmentioning
confidence: 98%